On Decolonisation and the University. Issue 6 (3rd June 2021) - Gopal, Priyamvada
ABSTRACT: Is 'decolonisation' relevant at all to the university situated in Britain and other former colonial centres? Answering broadly in the affirmative, this essay situates the project of 'decolonising' the metropolitan university within a wider historical and intellectual context while delineating some of the key questions such an endeavour might grapple with. It argues that 'Western' universities can lead the increasingly vital task of historical self-understanding in the constituent polities and societies of the geopolitical 'West'. Decolonisation is reparative of the 'European' itself, seeking to understand and to extend knowledge about how cultures and communities outside it have shaped 'Europe'. Reframing discussions of decolonisation in the light of anticolonial thought – as the theory and practice of anticolonialism – gives grounding, heft and direction to them, enabling rich questions to be posed and answered towards the wider horizon of making another world possible.